Involved margins after lumpectomy for breast cancer: Always to be re-excised?. (September 2019) - Sorrentino, Luca; Agozzino, Manuela; Albasini, Sara; Bossi, Daniela; Mazzucchelli, Serena; Vanna, Renzo; Papadopoulou, Ourania; Villani, Laura; Corsi, Fabio
Abstract: Background: The oncologic benefit of upfront re-excision of involved margins after breast-conserving surgery in the context of current multimodal clinical management of breast cancer is unclear. The aim of the present study was to assess the 5-years locoregional recurrence (LRR)-free and distant metastases (DM)-free survival probabilities in patients not undergoing re-excision of positive margins after lumpectomy for breast cancer. Methods: A cohort of 104 patients with positive margins not undergoing re-excision was matched by propensity score with a cohort of 2006 control patients with clear margins after breast-conserving surgery, treated between 2008 and 2018. A multivariate survival analysis was performed accounting for all variables related to LRR and DM, including adjuvant treatments. Results: After adjusting for potential confounders, avoiding to re-excise a positive margin after lumpectomy had no effect on 5-years LRR-free survival probability (HR 0.98, 95%CI 0.36–2.67, p = 0.96) or 5-years DM-free survival probability (HR 0.37, 95%CI 0.08–1.61, p = 0.18). No correlation was found between occurrence of LRR and number of involved margins (HR 1.28, 95%CI 0.10–12.4, Log-rank p = 0.83), or extension of infiltrating disease (HR 1.21, 95%CI 0.20–7.40, Log-rank p = 0.83), but a trend toward higher LRR probability was found for invasive ductal (HR 6.92, 95%CI 0.7–68.8, Log-rank p = 0.10) and invasive lobular cancer (HR 12.95, 95%CI 0.79–213.6, Log-rank p = 0.07) on positive margins. Conclusions: In the era of multimodal treatment of breast cancer and accurate strategies to reduce the probability of residual disease in the post-lumpectomy cavity, re-excision of positive margins might be omitted in selected patients with low-risk breast cancers. Highlights: The benefit of routine re-excision of positive margins after lumpectomy is unclear. Avoiding to re-excise a positive margin had not increased loco-regional recurrences. Avoiding re-excision of positive margins might be discussed for selected patients.